Physicochemical, microbiological and antimicrobial properties of commercial honeys from Portugal - Gomes, Susana Paula Martins (2010)
The present study aimed to characterize five commercial honeys available in the Portuguese market in respect to their floral origins, physicochemical parameters and microbial safety and commercial quality assessment. Pollen profile, colour, moisture content, ash, acidity, electrical conductivity, pH, reducing sugars, apparent sucrose and HMF were the parameters analysed in each honey sample. Aerobic mesophiles, moulds and yeasts, fecal coliforms and sulphite-reducing clostridia were the microbial contaminants of interest studied. The antimicrobial effect against four fermentative yeasts was determined. Concerning the physicochemical parameters, all honey samples were found to meet European Legislation (EC Directive 2001/110) for all parameters, except for HMF and apparent sucrose. Microbiologically, the commercial quality was considered good and all samples showed to be negative in respect to safety parameters. We also verified that the presence of honey differentially affected the growth of fermentative yeasts under study, depending on the type of yeast, but this growth was not significantly influenced by the type of honey used.